Material Handling Equipment Selection Using Analytical Hierarchy Process (AHP) Method - Ramadhan Setiyani, Denok; Sukarno, Iwan (Jurnal Logistik Indonesia, 2022)
This study discusses alternative decisions to choose a material handling equipment by considering various criteria according to PT. Semen Indonesia (Persero) needed. The purpose of this research is to obtain a decision regarding an effective and efficient forklift for handling goods at PT. Semen Indonesia (Persero), Tuban Factory. The method that will be used is the Analytical Hierarchy Process (AHP) to produce a decision regarding the forklift that is worth buying based on the weighting of the criteria for fuel, depreciation, and capacity using Expert Choice (EC) software. The results of this study are the ranking of forklift alternatives from the highest, namely the alternative type C forklift with a value of 0.607, the alternative type B forklift with a value of 0.218, and the alternative type A forklift with a value of 0.177. So it can be concluded that a good forklift to choose is a type C forklift which is a sit down counterbalance forklift with gas fuel, capacity of 5 tons and a residual value of Rp. 25,628,906.25.